Perancangan Ulang ruas jalan wonosari - semin sta 0+000 - 4+000 D.I Yogyakarta - Apriyadi Dwi Widodo (Jurusan T. Sipil Fakultas Teknik UMY, 2014)
Perancangan Ulang ruas jalan wonosari - semin sta 0+000 - 4+000 D.I Yogyakarta